2013
DOI: 10.1136/bmjopen-2012-002460
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of GP, NP and patient views about the use of rapid streptococcal antigen detection tests (RADTs) in primary care: ‘swamped with sore throats?’

Abstract: ObjectiveTo explore patient and healthcare professionals’ (HCP) views of clinical scores and rapid streptococcal antigen detection tests (RADTs) for acute sore throat.DesignQualitative semistructured interview study.SettingUK primary care.ParticipantsGeneral practitioners (GPs), nurse practitioners (NPs) and patients from general practices across Hampshire, Oxfordshire and the West Midlands who were participating in the Primary Care Streptococcal Management (PRISM) study.MethodSemistructured, face-to-face and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…It is possible that the diagnostic uncertainty leading to unnecessary antibiotic prescriptions in tonsillitis leaves room for an increased use of RADTs and, as a consequence, for a decreased use of antibiotics in risk-averse GPs using RADT. RADTs may indeed decrease diagnostic uncertainty, as suggested in the literature 6–9 12. RADTs allow the physician to differentiate between viral and bacterial (group A streptococcal infection) tonsillitis, whereas clinical findings do not allow a reliable distinction to be made between viral and bacterial tonsillitis 3.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the diagnostic uncertainty leading to unnecessary antibiotic prescriptions in tonsillitis leaves room for an increased use of RADTs and, as a consequence, for a decreased use of antibiotics in risk-averse GPs using RADT. RADTs may indeed decrease diagnostic uncertainty, as suggested in the literature 6–9 12. RADTs allow the physician to differentiate between viral and bacterial (group A streptococcal infection) tonsillitis, whereas clinical findings do not allow a reliable distinction to be made between viral and bacterial tonsillitis 3.…”
Section: Discussionmentioning
confidence: 99%
“…5,20 A more recent study found that UK clinicians were initially skeptical about the use of POCTs and experienced problems using them in practice; however, over time these issues diminished. 21 A third study 22 identified that clinicians' preferences for interventions changed after having experience in using the interventions. Clinicians initially favoured POCTs over communication skills; however, they reversed their preference after trials of both.…”
Section: Discussionmentioning
confidence: 99%
“…The STAR study evaluated a multifaceted educational intervention delivered through both online and outreach visit training, and was centred on communication skills. [16][17][18][19][20][21][22][23][24][25][26] Clinicians reported that communication skills training gave them an additional insight into their patients' agendas, which they felt would reduce future unnecessary consultations, but required an initial investment of longer consultations. The current study found that only a minority of clinicians specifically mentioned the advantage of the communication skills and most concentrated on the benefits of the patient booklet.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PCPs belonging in this group typically saw interventions as too costly or too time consuming to fit into usual practice: In the last cell, 'Interventions as unnecessary', PCPs choose not to integrate interventions into their own practice, but to accept their utility for other, mostly inexperienced, groups of prescribers. Specifically, this was the case with certain PCPs who reported that, although interventions were unnecessary for them, they did have 'a place within primary care', 38 as they could prove a useful tool for inexperienced practitioners (for example, newly qualified GPs) or new prescribers (for example, nurses).…”
Section: Synthesis Of Group 2 (Intervention) Studiesmentioning
confidence: 99%